(untitled) (Olhar de Professor, 2023)
This paper problematizes the didactics of historical-philosophical foundations in teacher training, taking official Brazilian documents, such as the BNCC 2015 and BNC 2019, as a starting point. The primary aim is to investigate the importance of historical-philosophical foundation content for the effectiveness of the didactic practice and the continued formation of these teachers, besides proposing a methodology of didactic work. In epistemological terms, the work is rooted in the dialectic relationship between theory and practice within the epistemology of education, materialized in the discipline of didactics, with an integrative literature review and the elaboration of teachers’ experiential knowledge as epistemetodologies. The study concludes by affirming the need for historical-philosophical foundations in the establishment of didactic awareness and the elaboration of teachers’ experiential knowledge. Furthermore, active learning methodologies are indicated as relevant resources for teaching the historical-philosophical foundations of education.